Host phenotype is associated with reduced survival independent of tumour biology in patients with colorectal liver metastases. Issue 1 (31st October 2018) - van Dijk, David P.J.; Krill, Matthew; Farshidfar, Farshad; Li, Ting; Rensen, Sander S.; Olde Damink, Steven W.M.; Dixon, Elijah; Sutherland, Francis R.; Ball, Chad G.; Mazurak, Vera C.; Baracos, Vickie E.; Bathe, Oliver F.
Abstract: Background: Most prognostic scoring systems for colorectal liver metastases (CRLMs) account for factors related to tumour biology. Little is known about the effects of the host phenotype to the tumour. Our objective was to delineate the relationship of systemic inflammation and body composition features [i.e. low skeletal muscle mass (sarcopenia) and low visceral adipose tissue (VAT)], two well‐described host phenotypes in cancer. Methods: Clinical data and pre‐operative blood samples were collected from 99 patients who underwent resection of CRLM. Pre‐operative computed tomography scans were available for 97 patients; body composition was analysed at the L3 level, stratified for sex and age. Clinicopathological variables, serum C‐reactive protein (CRP), and various body composition variables were evaluated. Overall survival was evaluated as a function of these same variables in multivariate Cox regression analysis. Results: Skeletal muscle was significantly correlated with VAT ( r = 0.46, P < 0.001). Of patients with sarcopenia, 35 (65%) also had low VAT. C‐reactive protein was elevated (≥5 mg/mL) in 42 patients (43.3%). Elevated CRP was more common in patients with sarcopenia (57.4% vs. 33.3%, P = 0.029). The most significant prognostic factors were the coincidence of elevated CRP and adverse body composition features (sarcopenia and/or low VAT; hazard ratio 4.3, 95% confidence interval 1.5–13.0, P = 0.008), as well as Fong clinical prognostic score (hazard ratio 2.9, 95% confidence interval 1.5–5.5, P = 0.002). Conclusions: Body composition in patients with CRLM is not directly linked to the presence of systemic inflammation. However, when systemic inflammation coincides with sarcopenia and/or low VAT, prognosis is adversely affected, independent of the Fong clinical prognostic score.